Immature Senile Cataract: Case Report - Adinda Nurqalbi Rusnaedi; Muhammad Fadly Hidayat (PSPP JOURNALS, 2026)
Senile cataract is a degenerative ocular condition characterized by lens opacity that leads to progressive visual impairment and remains the leading cause of blindness globally, particularly in developing countries. Aging is the primary cause, while systemic conditions such as hypertension significantly accelerate cataract formation through oxidative stress and metabolic disruption in the lens. This study employed a descriptive literature-based approach by reviewing relevant scientific articles, clinical reports, and epidemiological data related to cataract pathophysiology, risk factors, classification, diagnosis, and management, with emphasis on the role of hypertension and surgical interventions. The findings indicate that cataractogenesis is multifactorial, involving protein aggregation, lens hydration, and oxidative damage. Hypertension contributes through inflammatory pathways and impaired ion transport in lens epithelial cells. Cataracts are classified based on age of onset, morphology, and etiology, with senile cataracts being the most prevalent. Clinical manifestations include blurred vision, glare, and gradual vision loss. Diagnostic approaches include visual acuity testing and slit-lamp examination. Surgical management, particularly phacoemulsification and delayed sequential bilateral cataract surgery (DSBCS), provides effective visual restoration with minimal complications. Senile cataracts significantly impact quality of life, and hypertension is an important modifiable risk factor. Early detection, risk control, and appropriate surgical intervention are essential to prevent blindness and improve patient outcomes.